Effect of Balance Training with Swiss Ball on Gross Motor Skill of Children with Attention Deficit - Hyperactivity Disorder - Farideh Shafati; Ahmadreza Movahedi; Hamid Salehi (University of Tehran, 2015)
Fundamental motor skills are key components of motor development and are divided into two main sub groups including fine and gross motor skills. The main purpose of the present study was to determine the effect of balance training with Swiss ball (BTWSB) on gross motor skill of Children with Attention Deficit - Hyperactivity Disorder. Participants of the present study were three 6 to 8 years old children with Combined type of Attention Deficit - Hyperactivity Disorder (ADHD-C). This study was a single-subject study with multiple baseline design. Participants were required to exercise BTWSB for 9 weeks. Change in the gross motor skill of participants was assessed at one-week intervals using multiple baseline method. We administered Conners Parent Rating Scale (2003) and Broininks - Oseretsky Test Of Motor Proficiency (1978) to assess each outcome variable. The results of the data chart analysis based on descriptive statistics and visual analysis showed that BTWSB improved gross motor skill of all three participants (PND = 100% for all three participants). The results of this study indicate a positive effect of BTWSB on improving gross motor skill of Children with Attention Deficit - Hyperactivity Disorder.